Back to the beginning (Oxbow Books, 2012)
Ever since their first discovery, more than a century ago, the Minoan Palaces have dominated scholarship on the Cretan Bronze Age. Opinion long held that their first appearance, seemingly at the beginning of the Middle Bronze Age, marked a pivotal transformation point, during which the simple, egalitarian societies of the Early Bronze Age were transformed into something significantly more complex, hierarchical and civilised. Over the last three decades, however, theoretical developments, together with new research and discoveries, have so thoroughly undermined this conceptualisation of the Ear